On the estimation of the remainder term in the central limit theorem - Bikelis, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. Об оценке остаточного члена в центральной предельной теореме A. Bikelis. Liekamojo nario įvertinimo centrinėje ribinėje teoremoje klausimu